Symptom Levels in Care-Seeking Bangladeshi and Nepalese Adults With Advanced Cancer - Love, Richard Reed; Ferdousy, Tahmina; Paudel, Bishnu D.; Nahar, Shamsun; Dowla, Rumana; Adibuzzaman, Mohammad; Ahsan, Golam Mushih Tanimul; Uddin, Miftah; Salim, Reza; Ahamed, Sheikh Iqbal (Journal of global oncology, 2017)
Three-fourths of patients with advanced cancer are reported to suffer from pain. A primary barrier to provision of adequate symptom treatment is failure to appreciate the intensity of the symptoms patients are experiencing. Because data on Bangladeshi and Nepalese patients' perceptions of their symptomatic status are limited, we sought such information using a cell phone questionnaire. At tertiary care centers in Dhaka and Kathmandu, we recruited 640 and 383 adult patients, respectively, with incurable malignancy presenting for outpatient visits and instructed them for that single visit on one-time completion of a cell phone platform 15-item survey of questions about common cancer-associated symptoms and their magnitudes using Likert scales of 0 to 10. The questions were taken from the Edmonton Symptom Assessment System and the Brief Pain Inventory instruments. All but two Bangladeshi patients recruited agreed to study participation. Two-thirds of Bangladeshi patients reported usual pain levels ≥ 5, and 50% of Nepalese patients reported usual pain levels ≥ 4 (population differences significant at < .001). Bangladeshi and Nepalese adults with advanced cancer are comfortable with cell phone questionnaires about their symptoms and report high levels of pain. Greater attention to the suffering of these patients is warranted.